Isokinetic Quadriceps and Hamstring Peak Torque in Athletes Aged 10-50+: Preoperative Uninvolved Limb Reference Values for ACL Reconstruction - John D Kipp; Amy L Bednarek; Marc A Sherry; Michael W Keefe; Elizabeth S Chumanov (International Journal of Sports Physical Therapy, 2026)
Background Current recommendations for quadriceps and hamstring peak torque normalized to body mass after anterior cruciate ligament reconstruction are derived from athletes in the second and third decades of life. There is a paucity of literature exploring the relationship between sex, age, and peak torque normalized to body mass. Purpose The purpose of this study was to examine the relationship between age and isokinetic quadriceps and hamstring peak torque normalized to body mass, as well as the hamstrings-to-quadriceps ratio (H:Q ratio), and to evaluate differences between sexes, using the uninvolved limb from pre-ACLR testing Study Design Retrospective review of prospectively collected data. Methods Three hundred twenty-one athletes were identified in the UW Health Sports Rehabilitation Database that had a planned anterior cruciate ligament reconstruction and had undergone pre-operative isokinetic testing of their quadriceps and hamstrings at 60°/sec on their uninvolved limb between July 2021 and January 2026. For reporting purposes, athletes were grouped into the following age groups: 10-14, 15-19, 20-29, 30-39, 40-49, and 50+. Linear regression models were used to examine the relationships between age (continuous), sex (binary), and their interaction on quadriceps peak torque normalized to body mass (Nm/kg), hamstring peak torque normalized to body mass (Nm/kg), and the H:Q ratio. Results There is a linear decrease in quadriceps (β = –0.016 Nm/kg per year, p < 0.001) and hamstring (β = –0.009 Nm/kg per year, p < 0.001) peak torque normalized to body mass with age. Males have higher mean quadriceps and hamstring peak torque normalized to body mass at all ages compared to females, although this difference was not statistically significant. Age explained 25% and 24% of the variance in normalized peak torque for the quadriceps and hamstrings, respectively. H:Q ratios stayed relatively the same with age and sex. Conclusion As athletes age, their quadriceps and hamstrings peak torque normalized to body mass decreases. Clinicians should acknowledge these differences when making recommendations throughout anterior cruciate ligament reconstruction rehabilitation. Level of Evidence Level 3